Sierra Leone : First Review Under the Extended Credit Facility Arrangement, Request for Waiver for Nonobservance of Performance Criterion, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Sierra Leone. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
Actions by the new government since taking office in April 2018 helped to stabilize macroeconomic conditions, but the situation remains challenging. Overall growth remained subdued. While elevated, inflation is tracking down. Program performance is broadly on track, though progress on structural measures has been slower than anticipated. Healthy revenues and significant underspending resulted in a lower-than-programed fiscal deficit. All quantitative targets were met, except the end-December performance criterion on net domestic assets (NDA) of the central bank and the end-March indicative target on poverty-related spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet